PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO INTERAKTIF PADA MATA PELAJARAN INFORMATIKA KELAS X DI SMKN 1 BONJOL - Wiyatri, Rahmi; Junaidi, Satrio; Novita, Rini (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2023)
This study aims to develop valid and practical interactive video learning media for informatics subjects using the Powtoon and H5P applications. This research uses Research and Development (RD) research with the ADDIE development model which consists of 5 stages, namely: (1) Analysis (2) Design (3) Development (4) Implementation (5) Evaluation. The collection technique in the research was using a questionnaire. The results showed that interactive video learning media using the Powtoon and H5P applications based on the results of media validation by media experts obtained an average value of 0.82 in the "Valid" category, while the results of material validation by material experts obtained an average value of 0.88 with â€œValidâ€ category. The results of practicality by the teacher obtained an average value of 91.74% in the "Very Practical" category, while for student practical results an average value of 89.19% was obtained in the "Very Practical" category, so it can be concluded that interactive video learning media The informatics lesson developed was declared valid and practical as a learning medium.